Osteoarthritis and Glucosamine - Meral Kozakçıoğlu, (Archives of Rheumatology, 2009)
Osteoarthritis is the most common form of arthritis and a worldwide health problem. Many institutes and centers have been conducting research studies for years about the advantages of glucosamine sulphate derivatives and chondroitin sulphate on pain and deformities caused by osteoarthritis. The results of the research studies mentioned are discussed in this paper. The controlled, randomized, double blind research studies have shown chondroitin sulphate to have good symptomatic effects on osteoarthritis, although some controversies remain. New research studies have revealed that glucosamine sulphate and chondroitin sulphate both have a suppressor effect on the structural deformities of osteoarthritis. (Turk J Rheumatol 2009; 24: 94-7)